Production of molecularly imprinted polymer particles with amide-decorated cavities for CO2 capture using membrane emulsification/suspension polymerisation - Nabavi, Seyed Ali; Vladisavljevic, Goran T.; Wicaksono, Agni; Georgiadou, Stella; Manovic, Vasilije (Elsevier, 2016)
Highly uniform amide-based molecularly imprinted polymer (MIP) particles containing CO2-philic cavities decorated with amide groups were produced using membrane emulsification and subsequent suspension polymerisation. The organic phase containing acrylamide (functional monomer), oxalic acid (dummy template), ethylene glycol dimethacrylate (crosslinker) and azobisisobutyronitrile (initiator) dissolved in a 50/50 mixture (by volume) of acetonitrile and toluene (porogenic solvents) was injected through a microengineered nickel membrane with a pore diameter of 20 μm and a pore spacing of 200 μm into agitated 0.5 wt% aqueous solution of poly(vinyl alcohol) to form droplets that have been polymerised at 60 °C for 3 h. The volume median diameter of the droplets was controlled between 35 and 158 μm by shear stress at the membrane surface. The droplets maintained their physical stability during storage for 4 weeks and their size was independent of the dispersed phase content. The particle size after polymerisation was consistent with the initial droplet size. The particles were stable up to 210 °C and had a specific surface area of 239 m2/g and a CO2 capture capacity of 0.59 mmol/g at 273 K and 0.15 bar CO2 partial pressure.
Keywords: CO2 capture capacity; Molecularly imprinted polymer; Amide decorated cavities; Membrane emulsification; Suspension polymerisation; Acrylamide